The Pengembangan Perangkat Pembelajaran RBL – STEM dalam Pemanfaatan Botol Plastik Bekas sebagai Elektroskop Untuk Meningkatkan Literasi Perubahan Iklim Siswa - Moh. Samsul Arifin; Rina Sugiarti Dwi Gita; Eges Triwahyuni (Postgraduate, University of Mataram, 2026)
This study aims to develop RBL-STEM (Research-Based Learning–Science, Technology, Engineering, and Mathematics) learning kits that utilize recycled plastic bottles as electroscopes to improve climate change literacy among junior high school students. The research follows the ADDIE model, encompassing the stages of Analysis, Design, Development, Implementation, and Evaluation. Initial analysis revealed that students' climate change literacy remained low, laboratory facilities are limited, and science education tends to be overly theoretical. The developed kits consisted of lesson plans (RPP), teaching modules, experimental worksheets (LKPD), electroscope prototypes, and evaluation instruments. Expert validation confirmed that the kits are “highly feasible.” Implementation involving 70 students showed a significant improvement in climate change literacy, with average scores rising from 66.61 in the pretest to 82.19 in the posttest. A paired-sample t-test yielded a significance value of 0.000, indicating that the kits are effective in enhancing students’ understanding. Furthermore, observations of the learning process and feedback from both teachers and students fell into the “excellent” category. The novelty of this research lies in the integration of RBL-STEM with electroscope experiments made from recycled materials, directly addressing environmental issues. Overall, these learning kits have proven to be valid, practical, and effective, contributing to stronger climate change literacy and the application of sustainable science education.